PENGARUH MODEL PEMEBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SKI DI MTS. AT-THOLIBIN LAMPUNG UTARA - Riska Rojiatun; Baharudin Baharudin; Era Octafiona (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
This study aims to examine the effects of the Team Games Tournament (TGT) learning model on the learning outcomes of eighth-grade students in the subject of Islamic Cultural History (SKI) at MTs At-Tholbin in North Lampung. The approach used is quantitative with a quasi-experimental research design that includes a pre- and post-test. The study sample consists of two classes: Class VIII A as the experimental group, in which the TGT model was applied, and Class VIII B as the control group, in which conventional teaching took place. An essay test, whose validity and reliability had been verified, was used as the measurement instrument. Data analysis was performed using a t-test for independent samples. The result of the study yielded a significance value of 0.000 < 0.05, indicating a clear and significant difference in learning outcomes between the experimental group and the control group. This proved that the Team Games Tournament (TGT) learning model has a positive influence on students' learning outcomes in the subject of Islamic cultural history.